PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENGELOLAAN KEUANGAN DESA (Studi Empiris Seluruh Nagari Di Kecamatan X Koto Singkarak Kabupaten Solok) - Ediska Harosa Putri; Witra Maison; Rita Dwi Putri (Pusat Riset dan Inovasi Nasional, 2022)
his study aims to determine the Effect of Transparency (X1) on Village Financial Management (Y), the Effect of Accountability (X2) on Village Financial Management (Y). The results showed that Transparency (X1) had an effect on Village Financial Management (Y). This result is evidenced by the value of t_(count ) of 9,823 > t_table of 1,673 with a significance value of 0,000 < 0,05. While Accountability (X2) affects Village Financial Management (Y). This result is evidenced by the value of t_(count ) of 5,729 > t_table of 1,673 with a significance value of 0,000 < 0,05. After that, Transparency (X1), Accountability (X2) have a simultaneous effect on Village Financial Management (Y). This result is proven by having a value of F_(count ) 101,905> F_(table ) 3,17, with a significant value of 0,000 < 0,05.